The Influence of Transformational Leadership, Abilities and Motivation on Teacher Performance State Madrasah Aliyah Langkat District - Said, Salim; Siahaan, Amiruddin; Fadhli, Muhammad (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2024)
Abstract. This study attempts to ascertain the following: (1) The impact of transformational leadership on the performance of teachers at the Langkat Regency State Madrasah Aliyah; (2) The impact of ability on the performance of teachers at the Langkat Regency State Madrasah Aliyah; (3) The impact of motivation on the performance of teachers at the Langkat Regency State Madrasah Aliyah; and (4) The impact of ability, motivation, and transformational leadership on the performance of teachers at the Langkat Regency State Madrasah Aliyah. This study used an ex post facto model and was quantitative in nature. The population under investigation consisted of 210 individuals, and the sample size consisted of 136 respondents who were selected using the Krejcie & Morgan formula or table. The study's findings indicate that: (1) At Madrasah Aliyah Negeri Langkat Regency, transformational leadership (X1) has a positive and significant influence on teacher performance (Y), with a p value of 0.021, where the value is less than 0.05, indicating that transformational leadership affects performance. In the meanwhile, the test yielded a t-statistic value of 2.317, indicating that transformational leadership has a considerable impact on teacher performance (t-statistic value > 1.96). In other words, whether leadership is transformative. The better a leader demonstrates in Madrasah Aliyah Negeri Langkat Regency, the more likely it is that teachers will perform better in fulfilling their ooko k responsibilities; At Madrasah Aliyah Negeri Langkat Regency, ability (X2) has a positive and substantial effect on teacher performance (Y) with a p value of 0.000, where the value is less than 0.05, indicating that ability affects performance. In the meanwhile, the test yielded a t-statistic value of 4.092, indicating that it is more than 1.96. This implies that instructors will be able to carry out their tasks in accordance with their capacities given their current set of skills, which will impact the enhancement of teacher performance; (3) At Madrasah Aliyah Negeri Langkat Regency, motivation (X3) has a positive and substantial impact on teacher performance (Y), with a p value of 0.000, where the value is less than 0.05, indicating that motivation affects performance. In the meanwhile, the test yielded a result of 5.771 for the t-statistic, meaning that it is more than 1.96. This implies that a teacher's performance increases with the degree to which they use work incentive.Keywords: Transformational Leadership, Ability, Motivation and Teacher Performance.